Research trend of microbiota-gut-brain axis in Alzheimer’s disease based on CiteSpace (2012–2021): A bibliometrics analysis of 608 articles - Li, Zi-Long; Ma, Hao-Tian; Wang, Meng; Qian, Yi-Hua (Frontiers in Aging Neuroscience, 2022)
Background: Recently, research on the microbiota–gut–brain axis (MGBA) has received increasing attention, and the number of studies related to Alzheimer's disease (AD) has increased rapidly, but there is currently a lack of summary of MGBA in AD. Objective: To capture research hotspots, grasp the context of disciplinary research, and explore future research development directions. Methods: In the core dataset of Web of Science, documents are searched according to specific subject words. CiteSpace software is used to perform statistical analysis on measurement indicators such as the number of published papers, publishing countries, institutions, subject areas, authors, cocited journals, and keywords, and to visualize of a network of relevant content elements. Results: The research of MGBA in AD has shown an upward trend year by year, and the cooperation between countries is relatively close, and mainly involves the intersection of neuroscience, pharmacy, and microbiology. This research focuses on the relationship between MGBA and AD symptoms. Keyword hotspots are closely related to new technologies. Alzheimer’s disease, anterior cingulate cortex, inflammatory degeneration, dysbiosis, and other research are the focus of this field. Conclusion: The study revealed that the research and development of MGBA in AD rapidly progressed, but no breakthrough has been made in the past decade, it it still needs to be closely combined with multidisciplinary technology to grasp the frontier hotspots. Countries should further strengthen cooperation, improve the disciplinary system, and increase the proportion of empirical research in all research.